The effect of bimineralic composition on extensional processes at lithospheric scale. (19th August 2016) - Jammes, Suzon; Lavier, Luc L.
Abstract: We investigate how lithospheric scale compositional heterogeneities affect kilometric scale deformation processes. To this end, we perform numerical experiments of lithospheric extension in which we vary the Moho temperature and the mineralic composition of the mantle and the crust. In both the crust and the mantle, we use an explicit bimineralic composition by randomly distributing two mineral phases in the materials. Comparison of our models to simulations using an implicit bimineralic composite (one average viscous flow laws for a two‐phase aggregate) crust and mantle demonstrates that an explicit bimineralic composition assimilated to heterogeneities succeeds in explaining observations related to the formation of rifted margins such a: (1) the absence of a sharp deformation zone at the brittle ductile transition (BDT), (2) the initiation of the rifting process as a wide delocalized rift system with multiple normal faults dipping in both directions; (3) the development of anastomosing shear zones in the middle/lower crust and the upper lithospheric mantle similar to the crustal scale anastomosing patterns observed in the field or in seismic data; (4) the preservation of undeformed lenses of material leading to lithospheric scale boudinage structure and resulting in the formation of continental ribbons as observed along the Iberian‐Newfoundland margin. Key Points: Lithospheric bimineralic composition explains the absence of a sharp brittle ductile transition Development of anastomosing shear zone is observed in the crust and the mantle The preservation of undeformed lenses of material leads to lithospheric scale boudinage structure